Persepsi Generasi Z terhadap Literasi Pengelolaan Keuangan pada Konten Instagram Reels @mentorkeuangan - Tri Cahyo Prakoso; Zamzamy, Ahmad (Yayasan Perguruan Kampus, 2024)
This research explores Generation Z's perception of financial management literacy on Instagram Reels content @mentorkeuangan. This is related to Instagram Reels as a popular media among generation Z. Apart from that, the President of the Republic of Indonesia, Joko Widodo, is targeting the Financial Services Authority (OJK) to reach 90 percent financial inclusion by 2024. Mentor Keuangan is one of the content creators who shares financial literacy via Instagram Reels media. This research focuses on understanding and identifying how generation Z perceives financial management literacy on Instagram Reels @mentorkuangan. This research uses a perception analysis research method in the period 26 August to 30 October 2023. The results of the research show that the majority of generation Z have difficulty capturing the information or education conveyed by Mentor Keuangan. This happens because most generation Z consider Instagram Reels content to be too short so that the message conveyed by the Mentor Keuangan does not have a perception effect. Apart from that, Taufiq Ismail's presentation, as the content creator of Mentor Keuangan, was considered less convincing because his presentation was less than enthusiastic and not interesting to learn.